Peran Komunikasi Terapeutik Kader Desa Terhadap Peningkatan Kesejahteraan Psikologis Orang Dengan Gangguan Jiwa Di Desa Blumbungan - Ummu Fadila Ulfa; Sri Wahyuningsih; Dessy Trisilowaty; Retno Hendariningrum (Jurnal Keperawatan Muhammadiyah, 2026)
Background: . The background of the study stems from limited access to mental health services in rural areas and the high stigma against ODGJ. Objective: to explore the role of therapeutic communication by village cadres in improving the psychological well-being of ODGJ in Blumbungan Village, Pamekasan. Methods: The study used a descriptive qualitative approach with in-depth interviews with cadres, ODGJ, families, and community leaders. Results: .The results showed that cadres implemented therapeutic communication through empathy, active listening, emotional validation, and motivation. The therapeutic communication of village cadres, characterized by empathy, trust, honesty, validation, and concern, contributed to improving the psychological well-being of ODGJ. From the perspective of George Herbert Mead's Symbolic Interactionism, this interaction helps shape a more positive self-meaning and increases social acceptance. This strategy increases openness, self-confidence, and self-acceptance of ODGJ and reduces the emotional burden on families. In addition, cadres serve as liaisons with formal health services. However, communication is sometimes accompanied by social control approaches such as intimidation, which is considered relevant in the Madurese cultural context. Conclusion: The study concluded that therapeutic communication by village cadres contributes significantly to psychosocial recovery, while also emphasizing the need for ongoing training and policy support.